The present state of aspirin and clopidogrel resistance - Guyer, K. E. (Hämostaseologie, 2009)
Antiplatelet therapy has demonstrated significant clinical benefit in the treatment of acute coronary syndrome. However, as with any treatment strategy it has been unable to prevent all cardiovascular events. This is far from surprising when considering the complexity of arterial thrombosis and more specifically platelet physiology. This lack of treatment success has provoked the introduction of various diagnostic tests and testing platforms with the intent of guiding and optimizing clinical treatment. Such tests have resulted in the generation of clinical data that suggest suboptimal response to antiplatelet agents such as aspirin and clopidogrel.In the case of both aspirin and clopidogrel, this suboptimal response has been termed resistance. Drug resistance would imply a lack of pharmacological response that has not been specifically investigated in many of the clinical studies performed to date. Rather, the term resistance has been used to describe various facets of platelet activation and aggregation relative to the testing method. Many of these measured parameters are not addressed in the therapeutic intent of the antiplatelet drug in question.
Keywords: Aspirin; clopidogrel; resistance; monitoring